2010
DOI: 10.15845/voices.v10i2.164
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Group Musical Activity on Psychiatric Patients in India.

Abstract: Musical activity, particularly as the application of music therapy, has been found to produce numerous benefits within a psychiatric setting. This study has explored a selection of these benefits in psychiatric patients in a hospital in India, examining these effects within a culture not typically studied in this field. Observation of seven sessions of group musical activity was undertaken and questionnaire and interview data collected from both patients and staff. Questionnaire data demonstrated improvements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The assumptions revealed in the seven music therapy studies were related to the role of the therapist rather than the music, and particularly the belief that the therapeutic relationship serves as a safe container for diverse experiences of emotions through music (Ansdell et al, 2010; Gardstrom, Bartkowski, Willenbrink, & Diestelkamp, 2013; Rumball, 2010; Solli et al, 2013; Trondalen & Skarderud, 2007). Idiographic approaches serve to unearth complex and contextualised understandings of individual experiences.…”
Section: Resultsmentioning
confidence: 99%
“…The assumptions revealed in the seven music therapy studies were related to the role of the therapist rather than the music, and particularly the belief that the therapeutic relationship serves as a safe container for diverse experiences of emotions through music (Ansdell et al, 2010; Gardstrom, Bartkowski, Willenbrink, & Diestelkamp, 2013; Rumball, 2010; Solli et al, 2013; Trondalen & Skarderud, 2007). Idiographic approaches serve to unearth complex and contextualised understandings of individual experiences.…”
Section: Resultsmentioning
confidence: 99%
“…[75] Used Indian classical music in treatment of Depression. [76] worked in a similar area with Schizophrenia and Depression. [77] Showed significantly better improvement in patients with Depression while using music for their treatment rather than those who received only psychotropic medications.…”
Section: Discussionmentioning
confidence: 99%
“…Depression scores improved with the music group comparable to the control group and these effects persisted beyond the treatment period. Four out of the 18 participants, included in the other Indian study by Rumball,[ 79 ] were diagnosed of depression and all four of them scored significantly lesser depression scores on the self-rated questionnaire both during and after the sessions. Major limitations of this study were lack of randomization and extremely small sample size.…”
Section: Music Therapymentioning
confidence: 99%
“…Among the two published studies is Rumball,[ 79 ] which studied nine schizophrenia patients and found that in all the nine patients “energy” (sluggishness) improved and this was implicated as improvement in negative symptoms. Study by De souse and De souse[ 100 ] is the largest randomized control trial in terms of sample size (272 chronic schizophrenia patients).…”
Section: Music Therapymentioning
confidence: 99%